Konseling Feminis Untuk Pemulihan Korban Kekerasan seksual - Silmi Riasah Priyatna; Muhammad Zulfikar; Muhammad Alridho Lubis (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
Data on sexual violence has increased. Specifically, sexual violence against women in the school setting. This paper discusses the provision of responsive service assistance that can be carried out by school counselors in schools for the recovery of victims of sexual violence with a feminist counseling approach. Feminist counseling for victims of sexual violence is used to help victims become androgynous, creative, productive, active, and independent, and to build a self-image of women who are able to optimally actualize their potential.